Eksistensi Material Komposit Guna Menunjang Alutsista Pertahanan Negara - Hutagalung, Ananda Yessica Margaretha; Aritonang, Sovian; Murniati, Riri (Fakultas Teknik UMSU, 2025)
Composite materials have become an important aspect in the development of national defense equipment. In an effort to improve the performance and effectiveness of the main weapons system (alutsista), the application of composite materials has become a significant solution. This research aims to review the existence of composite materials in supporting national defense, focusing on the benefits, characteristics and important role in achieving excellence in defense equipment. The advantages of composite materials include strength, hardness, corrosion resistance, and lighter weight than traditional metals. With these characteristics, composite materials have had a positive impact on the development of national defense equipment. In a world that continues to change and becomes increasingly complex, the existence of composite materials in national defense equipment is a strategic step to maintain and increase military deterrence and effectiveness. This research will explain the role of composite materials in achieving this goal, as well as review the latest developments in the use of composite materials in the defense sector.